HIV/AIDS in the Caribbean : issues and options (World Bank WashingtonUS, 2000)
Provides an overview of the challenges and oppotunities in addressing the problem of HIV/AIDS in the Caribbean. Presents a snapshot of the HIV/AIDS epidemic in the region. Offers examples of ways in which Caribbean countries and regional bodies such as CARICOM have responded to the epidemic. Discusses alternative actions for addressing the crisis, and highlights a range of strategies for donor coordination and cooperation in the region. Identifies the potential role of the world Bank in addressing the HIV/AIDS epidemic in the Caribbean.
Located in the Office of the Secretary-General